(untitled) (Global Journal of Medical Research, 1970)
Cystic fibrosis CF the most common genetic disorder among the Caucasian population was believed to be extremely rare or non-existent in Indian subcontinent countries like Bangladesh But the real scenario is not so infrequent as per belief